Effect of Surface Roughness on Adhesion Strength and Corrosion Resistance of Silica-Epoxy Composite Coated Low Carbon Steel - Tresna, Rizal; Amrullah, Keanu Rafi; Rahmatullah, Aqil; Febriana, Eni; Lalasari, Latifa Hanum; Riastuti, Rini (Metalurgi, 2024)
Low-carbon steel is widely used in various industries but is susceptible to corrosion in aggressive environments, prompting this study on an epoxy-silica composite coating with variations in silica concentration (0-5 wt.%), sonication dispersion, and surface preparation (abrasive blast cleaning and power tool cleaning); the results showed that abrasive blast cleaning produced a surface roughness of 79 µm and superior adhesion strength (10.48 MPa) compared to power tool cleaning, with a perfect 5A rating in the x-cut tape test for all silica concentrations, while the highest adhesion strength of 14.33 MPa was achieved at 3 wt.% silica, and coating durability tests revealed the best performance exhibiting minimal corrosion propagation of only 0.55 mm after 72 hours at 5 wt.% silica in scratch tests using abrasive blast cleaning, underscoring the significant influence of surface preparation method on coating performance.